Antimicrobial resistance profile of Staphylococcus aureus and its in-vitro potential inhibition efficiency - Khaloud M. Alarjani; Milan Skalicky (Elsevier, 2021)
Background: Staphylococcus aureus infection is associated with hospitals and caused mortality in hospitalized patients. These biofilm-forming bacteria are associated with chronic infections in patients. Objectives: To investigate the biofilm forming ability of multidrug resistant bacteria associated with hospital environment and analyze anti-biofilm compounds from the natural sources. Methods: The hospital wastewater sample was used for the isolation of drug resistant S. aureus strains. The biofilm producing ability was analyzed and the isolated S. aureus strains were tested for antibiotic susceptibility patterns against various antibiotics. To screen suitable antibacterial agent, essential oil was extracted from Teucrium polium by hydrodistillation method and the compounds were determined by GC-MS analysis. The antimicrobial potential of essential oil was studied against S. aureus strains by disc diffusion method and biofilm inhibition property of essential oil was analyzed. The synergistic activity of essential oil was also analyzed. Results: A total of 13 S. aureus strains were isolated and almost all bacterial strains showed biofilm forming ability. Most of the isolated S. aureus strains showed resistance to ampicillin, cefoxitin, ciprofloxacin, erythromycin, gentamicin, chloramphenicol and vancomycin. The extracted essential oil showed pale yellow in colour with pleasant odour and the yield was about 0.9%. Twenty-two compounds were detected in GC-MS analysis which shared about 96% of the total determined chemical composition. The major compounds determined were α-pinene (5.3%), linalool (16.2%), caryophyllene (10.04%), germacrene D (37.2%), and β-eudesmol (6.1%). The extracted essential oil showed antibacterial activity and the zone of inhibition varied from 15 ± 1 to 21 ± 2 mm against S. aureus strains. The essential oil showed antibiofilm activity and synergistic activity against S. aureus strains. Conclusions: This study analyzed biofilm forming ability of drug resistant S. aureus strains isolated from the hospital wastewater. The isolated bacterial strains showed resistance against various tested antibiotics. The essential oil extracted from T. polium showed antibacterial and anti-biofilm activity.